Asymmetric Michael Addition of Unactivated Ketones with β‐Nitrostyrenes Mediated by Bifunctional L‐Prolinamide Organocatalysts. Issue 8 (24th February 2020) - Rani, Dixita; Bhargava, Meha; Agarwal, Jyoti
Abstract: The catalytic activity of two types of L‐prolinamide organocatalysts was investigated for asymmetric Michael addition reaction of cyclic/acyclic ketones with β‐nitrostyrens. L‐Prolinamides bearing amino groups on phenyl ring worked well, though their catalytic efficiency as well as selectivity was found to be dependent upon the position of amine group to the amide bond. Organocatalyst having –NH2 group ortho to amide bond provided the best results. Substrate scope was also studied by performing the reaction of various β‐nitrostyrenes with ketones to afford the corresponding Michael adducts in excellent yields with very high diastereoselectivities and enantioselectivities in almost all cases. Abstract : The catalytic activity of L‐prolinamide organocatalysts bearing amino groups on phenyl ring was investigated for the asymmetric Michael addition of acyclic/cyclic ketones with β‐nitrostyrens. Their catalytic efficiency in terms of chemical as well as optical yields was dependent upon the position of amine group to the amide bond and the organocatalyst having –NH2 group ortho to amide bond provided the best results. In almost all cases, Michael adducts were achieved in excellent yields with very high diastereo‐ and enantio‐selectivities.